2010
DOI: 10.1128/cvi.00328-09
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Immune Responses of Preterm Infants after Vaccination with Whole-Cell or Acellular Pertussis Vaccines

Abstract: Based on studies reporting specific antibody titers, it is recommended to vaccinate preterm infants against Bordetella pertussis according to their chronological age. However, as specific T-cell responses also are involved in the protection against B. pertussis, we have determined whether highly preterm infants (<31 weeks) are able to mount these immune responses during vaccination. Forty-eight premature infants were vaccinated at 2, 3, and 4 months of their chronological age with an acellular (Pa; n ‫؍‬ 24) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 26 publications
2
32
0
2
Order By: Relevance
“…In contrast, acellular pertussis vaccines appear to induce a predominantly Th-2 CD4-positive cellular immune response (408,411,(416)(417)(418). However, in other studies, a Th-1 or a mixed Th-1/Th-2 response was also observed after three-component acellular pertussis vaccination (406,411,(419)(420)(421)(422)(423)(424).…”
Section: Vaccine-induced Immunitymentioning
confidence: 72%
“…In contrast, acellular pertussis vaccines appear to induce a predominantly Th-2 CD4-positive cellular immune response (408,411,(416)(417)(418). However, in other studies, a Th-1 or a mixed Th-1/Th-2 response was also observed after three-component acellular pertussis vaccination (406,411,(419)(420)(421)(422)(423)(424).…”
Section: Vaccine-induced Immunitymentioning
confidence: 72%
“…97% of premature infants with GA <30 weeks had protective titers to 3 poliovirus types [31] after the 3 rd vaccine administration dose (scheme -2-3-4 months). Along with humoral antibodies, premature infants respond with the secretion IgA-antibody titer increase to the same extent as term infants [32]. The aforementioned study by N.P.…”
Section: Immunogenicity and Reactogenicity In Premature Infantsmentioning
confidence: 86%
“…However, HBV causes the same response in premature children as in term infants from 1 month of age regardless of GA and birth weight. Various schemes have been tested in this respect, including scheme 2-4-6 months, which produced the results comparable with the results in term infants [15,[31][32][33][34]. The given data served as the basis for formulation of vaccination tactics for premature infants.…”
Section: Immunogenicity and Reactogenicity In Premature Infantsmentioning
confidence: 92%
“…Studies in very young children (2 months of age) show that natural infection with B. pertussis or a first administration of WCV can promote maturation of Th1-type responses [61,62]. By contrast, the widely used ACV vaccines also induce Th2-type cytokine (IL-4 and IL-5) responses to concomitant vaccine antigens in infants [60,62], becoming more pronounced when given closer to birth [63,64]. Although suggested earlier, current infant immunization with ACV does not seem to be a risk factor for the development of atopic disease in children [65,66], despite similarities in Th2 polarization of vaccine-induced and allergic T-cell responses.…”
Section: Induction and Maintenance Of Pertussis Immunitymentioning
confidence: 99%